A self-powered sterilization system with both instant and sustainable anti-bacterial ability. (June 2017) - Tian, Jingjing; Feng, Hongqing; Yan, Ling; Yu, Min; Ouyang, Han; Li, Hu; Jiang, Wen; Jin, Yiming; Zhu, Guang; Li, Zhou; Wang, Zhong Lin
Abstract: A self-powered and high-efficient water sterilization system was set up consisting of a wave-driven triboelectric nanogenerator (TENG) and two nanobrush electrodes made of Ag-nanoparticles integrated ZnO-nanowires. The system showed both instant and sustainable sterilization efficiency for various microbes including those in natural river water. The colony forming units (CFU) were reduced from 10 6 /mL to 0 within 0.5 min of electrical field (EF) treatment for Gram-negative bacteria. In addition, the bacteria annihilation ability was sustained for at least 20 min after withdrawing the EF. The mechanism lay in the synergetic work of electricity and the Ag/ZnO nanomaterial, which not only produced electroporation during EF treatment, but also induced sustained intracellular reactive oxygen species (ROS) to do additional sterilization when EF was withdrawn. Graphical abstract: The synergetic work of the electricity produced by TENG and the Ag/ZnO nanobrush electrodes enables both instant and sustainable water sterilization. Highlights: This water sterilization system is self-powered by utilizing a wave-driven TENG. This system can reduce the number of bacteria from 10 6 /ml to 0 within 0.5 min of EF treatment due to electroporation effect. This system can maintain the sterilization ability for 20 min after the EF is withdrawn due to induction of ROS. The induction of reactive oxygen species is caused by the electron storage property of the Ag/ZnO nanobrush electrodes.